2002
DOI: 10.3201/eid0802.010145
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antibiotic Resistance of Diarrheal Pathogens from Vietnam and Thailand, 1996-1999

Abstract: Antimicrobial resistance rates for shigella, campylobacter, nontyphoidal salmonella, and enterotoxigenic Escherichia coli were compared for Vietnam and Thailand from 1996 to 1999. Resistance to trimethoprim-sulfamethoxazole, ampicillin, chloramphenicol, and tetracycline was common. Quinolone resistance remains low in both countries, except among campylobacter and salmonella organisms in Thailand. Nalidixic acid resistance among salmonellae has more than doubled since 1995 (to 21%) in Thailand but is not yet do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 23 publications
4
96
2
2
Order By: Relevance
“…at the farm [20]. Low levels of ciprofloxacin resistance were observed, which was comparable to other studies of humans and foods [4,14]. However, the prevalence of ciprofloxacin resistance from this study was slightly higher in comparison to the earlier study in farm sectors, where no resistance to the agent was found [20].…”
Section: Discussioncontrasting
confidence: 51%
“…at the farm [20]. Low levels of ciprofloxacin resistance were observed, which was comparable to other studies of humans and foods [4,14]. However, the prevalence of ciprofloxacin resistance from this study was slightly higher in comparison to the earlier study in farm sectors, where no resistance to the agent was found [20].…”
Section: Discussioncontrasting
confidence: 51%
“…A high prevalence of nalidixic acid and fluoroquinolone-resistant Campylobacter has been well-documented in Thailand. [24][25][26] Resistance of Campylobacter isolates to nalidixic acid increased significantly during 1991-2000, with isolates resistant to both nalidixic acid and ciprofloxacin observed significantly more frequently in urban than in rural settings. 24 Ongoing antimicrobial surveillance may permit more effective therapy in remote areas.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on isolation of Campylobacter from poultry meat have been carried out from the regions Tamilnadu and Calcutta using conventional method (Chowdhury et al, 1984;Varma et al, 2000). Although Campylobacter with resistance to antimicrobial agents has been reported worldwide (Looveren et al, 2001;Isenbarger et al, 2002), the situation seems to deteriorate more rapidly in developing countries, where there is widespread and uncontrolled use of antibiotics (Hart and Kariuki, 1998). Moreover, Campylobacter infections pose a serious public health problem for which many countries are monitoring their infection and antimicrobial resistance patterns.…”
Section: Introductionmentioning
confidence: 99%